2020
DOI: 10.1111/jrh.12529
|View full text |Cite
|
Sign up to set email alerts
|

Georgia Rural Hospital Tax Credit: Perspectives of Rural Health Executives

Abstract: Purpose In 2016, Georgia implemented a rural hospital tax credit program through a legislative mandate that allows individuals and corporations to donate to qualifying rural hospitals in exchange for state income tax credit. The study examines the importance, success, and challenges of the program, and opportunities for improvement, from the perspective of Georgia rural hospital executives. Methods The study was a qualitative study using data from key informant telephone interviews with 21 hospital executives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…A previous study of Georgia rural hospital executives 8 noted decreases in donations in program (calendar) year 2019 compared with 2018 levels as the federal tax credit reform went into effect. 8 Donations decreased by approximately $10 million ($59.5 million in 2018 vs $49.4 million in 2019). 20 Because of the misalignment between the Rural Hospital Tax Credit Program year and most hospitals’ fiscal years, these declines will most likely be reflected in fiscal year 2020 hospital cost-report data.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…A previous study of Georgia rural hospital executives 8 noted decreases in donations in program (calendar) year 2019 compared with 2018 levels as the federal tax credit reform went into effect. 8 Donations decreased by approximately $10 million ($59.5 million in 2018 vs $49.4 million in 2019). 20 Because of the misalignment between the Rural Hospital Tax Credit Program year and most hospitals’ fiscal years, these declines will most likely be reflected in fiscal year 2020 hospital cost-report data.…”
Section: Discussionmentioning
confidence: 95%
“…7 Recent evidence suggests that Georgia's Rural Hospital Tax Credit Program may help struggling rural hospitals in the state. A previous qualitative study of the program 8 reported favorable perceptions about the program among Georgia rural hospital executives, who described the program as an important lifeline, especially for severely struggling hospitals. They reported investing donations from the program directly into hospital operations and growth efforts, including servicing debt, supporting service expansion efforts, and investing in technology and capital infrastructure.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations